The Long-run Relationship between Real Exchange Rate and Real Interest Rate in Asian Countries: An Application of Panel Cointegration (The Pakistan Development Review, 2001)
The role of exchange rate policy in economic development has been the subject of much debate and controversy in the development literature. Interest rates and exchange rates are usually viewed as important in the transmission of monetary impulses to the real economy. In the short run the standard view of academics and policy-makers is that a monetary expansion lowers the interest rate and rises the exchange rate, with these price changes then affecting the level and composition of aggregate demand. Frequently, these influences are described as the liquidity effects of monetary expansion, viewed as the joint effect of providing larger quantities of money to the private sector. Popular theories of exchange-rate determination also predict a link between real exchange rates and real interest rate differentials. These theories combine the uncovered interest parity relationship with the assumption that the real exchange rate deviates from its long-run level only temporarily. Under these assumptions, shocks to the real exchange rate—which are often viewed as caused by shocks to monetary policy—are expected to reverse themselves over time. This study investigates the long-run relationship between real exchange rates and real interest rate differentials using recently developed panel cointegration technique. Although this kind of relationship has been studied by a number of researchers,1 very little evidence in support of the relationship has been reported in the case of developing countries. For example, Meese and Rogoff (1988) and Edison and Pauls (1993), among others, used the Engle-Granger cointegration method and fail to establish a clear long-run relationship in their analysis.